Psych. The complete fourth season [videorecording (DVD)] - Bernsen, Corbin, 1954-; Hill, Dulé; Roday, James (Universal, 2010)
Detective Shawn Spencer opens an agency where he offers his psychic services. The only problem is that Shawn's not psychic.